Efficacy of Extracts of Cyanthillium Cinereum, Khaya senegalensis and Lippia multiflora on Candida Strains Isolated From Urine Samples in Benin (West Africa) - Fanou, Brice Armand; Klotoe, Jean Robert; Dougnon, Victorien; Assogba, Phénix; Agbodjento, Eric; Koudokpon, Charles Hornel; Fah, Lauris; Sintondji, Kévin; Kpoze, Rodrigue; Loko, Frédéric (Frontiers in Tropical Diseases, 2022)
The search for new bioactive molecules with antifungal properties to combat resistance to classical antifungals represents a great challenge. This study aimed to explore the virulence factors and resistance profile of Candida species isolated from urine samples in Benin and the in vitro efficacy of organic extracts of Cyanthillium cinereum (L.) H.Rob., Lippia multiflora Moldenke and Khaya senegalensis (Desv.) A.Juss. on the growth of these Candida spp. The study focused on Candida strains isolated from urine samples collected from patients admitted to the bacteriological analysis laboratories of hospitals in South Benin. The sensitivity of these strains to classical antifungal agents was determined by the simple diffusion method. Their pathogenicity was investigated via several virulence factors (gelatinase, hemolysin, hydrophobicity, adhesin, biofilm and lecithinase). The in vitro efficacy of the aqueous, ethanolic and hydro-ethanolic extracts of the plants on Candida albicans ATCC 90028 and on six clinical strains was evaluated by the method of determination of the inhibition diameters. The results obtained showed that 51 different Candida strains were isolated from the collected urine samples with a respective predominance of Candida albicans (52.94%) and Candida glabrata (17.64%) species. All identified species were sensitive to amphotericin B and nystatin but 20% are resistant to fluconazole and present 15 different resistance profiles. Six different virulence factors were identified with a high frequency of hydrophobicity (96.08%) and adhesin (94.12%). Antifungal tests revealed that at 100 mg/mL the plant extracts were active on the tested strains with better activity for Cyanthilium cinereum and Khaya senegalensis. Cyanthilium cinereum, Khaya senegalensis and Lippia multiflora showed antifungal activity on virulent Candida strains suggesting the possibility to explore them further for the discovery of new antifungal molecules.